„Nones” (bezwyznaniowi) jako wyzwanie dla tradycyjnych form przynależności religijnej - Obirek, Stanisław (Humaniora. Czasopismo Internetowe, 2026)
This article attempts to present the theoretical and practical implications of the emergence of the “nones” group. According to the author, it is both a real opportunity and a challenge for traditional and institutional forms of religion. The opportunity lies in drawing attention to the possibility of enriching existing institutional forms of religion with a critical view of existing forms, while the challenge concerns a radical questioning of the need for the mediation of religious institutions and the forms they have developed to satisfy spiritual needs. These considerations are complemented by a reflection on the necessity of scientific analysis of the phenomenon of religion and unbelief.